2018
DOI: 10.1002/anie.201812642
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Chirality and Sequential Energy Transfer in a Supramolecular Light‐Harvesting Nanotube

Abstract: By constructing a supramolecular light‐harvesting chiral nanotube in the aqueous phase, we demonstrate a cooperative energy and chirality transfer. It was found that a cyanostilbene‐appended glutamate compound (CG) self‐assembled into helical nanotubes exhibiting both supramolecular chirality and circularly polarized luminescence (CPL). When two achiral acceptors, ThT and AO, with different energy bands were co‐assembled with the nanotube, the CG nanotube could transfer its chirality to both of the acceptors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(141 citation statements)
references
References 47 publications
1
132
0
1
Order By: Relevance
“…[34] To further investigate the amplification of CPL based on energy transfer, we recently reported a cooperative chirality and sequential energy transfer in a supramolecular light-harvesting nanotube, which contained a cyanostilbene-appended glutamate hydrogelator (CG) and two achiral acceptors, thioflavin T (ThT), and acridine orange (AO). [35] As illustrated in Figure 15B, the chiral gelator could self-assemble into helical nanotubes exhibiting both supramolecular chirality and CPL. When two achiral acceptors were coassembled with the CG nanotubes, the chiral information could transfer to both of the acceptors.…”
Section: Cpl Amplified By Förster Resonance Energy Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…[34] To further investigate the amplification of CPL based on energy transfer, we recently reported a cooperative chirality and sequential energy transfer in a supramolecular light-harvesting nanotube, which contained a cyanostilbene-appended glutamate hydrogelator (CG) and two achiral acceptors, thioflavin T (ThT), and acridine orange (AO). [35] As illustrated in Figure 15B, the chiral gelator could self-assemble into helical nanotubes exhibiting both supramolecular chirality and CPL. When two achiral acceptors were coassembled with the CG nanotubes, the chiral information could transfer to both of the acceptors.…”
Section: Cpl Amplified By Förster Resonance Energy Transfermentioning
confidence: 99%
“…Polarization of light can be regarded as part of a high-level visual perception since it contains a lot of potentially useful information about such visual features like the material content, surface shape, and local curvature of objects. [1] Among the different kinds of polarized light, circular polarized light is considered to be special, and has drawn great attention due to its potential application in 3D displays, [2,3] chiroptical materials, [4] although some other exciting strategies, including plasmon resonance, [33] Förster resonance energy transfer (FRET), [34,35] triplet-triplet-annihilation-based photon upconversion (TTA-UC) [36] and liquid crystals, [37][38][39] have also been reported as reliable pathways for amplifying the g lum value.…”
Section: Introductionmentioning
confidence: 99%
“…We now provide brief comment on some recent innovative experimental investigations on chirality. 84,85 It is evident, in these reports, that the concepts of 'chirality transfer' or 'chiral energy' are deployed as descriptors. However, such terms are misleading and we suggest their usage is inadvisable.…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al have recently reported chiral light-harvesting nanotube antennas and studied cooperative assembly and energy transfer amongst its water soluble donor and acceptor components. 85 In their work, cyanostilbene-appended glutamate (CG) self-assembled into helical nanotubes, as seen in SEM and TEM, whose chirality was controlled by switching between L-CG and D-CG (Fig. 8A).…”
Section: Förster Resonance Energy Transfermentioning
confidence: 94%